The role of family doctors in the management of domestic violence cases - a qualitative study in Portugal - Diana Nadine Moreira; Mariana Pinto da Costa (BMC, 2023)
Abstract Background Domestic violence leads to multiple health problems in victims and their families. Family doctors are in a particularly privileged position to detect, follow up, refer and report cases of domestic violence. However, little is known about the perception of these physicians regarding their role in managing domestic violence cases. Methods We conducted semi-structured interviews with family doctors from all regional health administrations of continental Portugal. Interviews were audio recorded, transcribed, and analysed using thematic analysis. Results Fifty-four family doctors participated in this study (n = 39 women, n = 15 men). The themes and subthemes that emerged from the data analysis translated doctors' broad responsibilities when approaching victims and aggressors. These included: "Implement preventive measures", "Empower the victim leading them to recognize the violent situation", "Detect domestic violence cases", "Treat health problems related to violence", "Provide emotional support", "Refer victims to specialized services", "Register the episode on the victims and/or aggressor clinical records", "Incentivize the victim to report", "Report the case to the authorities", "Intervene with the aggressor", "Protect other individuals" and "Follow up the patient and the process". Conclusions The results of this study provide an overview of the current practical approaches being adopted by physicians and may provide a base for developing new interventions to support physicians to manage cases of domestic violence.